Targeted Protein Degradation by Chimeric Compounds using Hydrophobic E3 Ligands and Adamantane Moiety - Takuji Shoda; Nobumichi Ohoka; Genichiro Tsuji; Takuma Fujisato; Hideshi Inoue; Yosuke Demizu; Mikihiko Naito; Masaaki Kurihara (MDPI AG, 2020)
Targeted protein degradation using small chimeric molecules, such as proteolysis-targeting chimeras (PROTACs) and specific and nongenetic inhibitors of apoptosis protein [IAP]-dependent protein erasers (SNIPERs), is a promising technology in drug discovery. We recently developed a novel class of chimeric compounds that recruit the aryl hydrocarbon receptor (AhR) E3 ligase complex and induce the AhR-dependent degradation of target proteins. However, these chimeras contain a hydrophobic AhR E3 ligand, and thus, degrade target proteins even in cells that do not express AhR. In this study, we synthesized new compounds in which the AhR ligands were replaced with a hydrophobic adamantane moiety to investigate the mechanisms of AhR-independent degradation. Our results showed that the compounds, 2, 3, and 16 induced significant degradation of some target proteins in cells that do not express AhR, similar to the chimeras containing AhR ligands. However, in cells expressing AhR, 2, 3, and 16 did not induce the degradation of other target proteins, in contrast with their response to chimeras containing AhR ligands. Overall, it was suggested that target proteins susceptible to the hydrophobic tagging system are degraded by chimeras containing hydrophobic AhR ligands even without AhR.